MOTIVASI MAHASISWA BERWIRAUSAHA DI PERGURUAN TINGGI SWASTA KOTA PALEMBANG - Safitri, Ervita (Jurnal Ilmu Manajemen, 2013)
The research problem 1) How is the enterpreneurship in Palembang 2) Is there differrence in enterpreneurship student. The research goals is to know the enterpreneurshipstudent and the differrence in enterpreneurship student.Design conclusive has been used in this research. There is one variable, student motivation. The variable is broadened to: financial compensation, prestice, time demand, lifequality, risk, guarantee, capital, and backup. All private university student in palembang is the population. Three hundreds and fifty students are the sample. The methode to choose the sample is cluster sampling. The main data is primary data. That is responden answer from the questionare. The data analizes question is proportion analisis technique and Chi Square. The result of the research: 1) There is 68,6% of Palembang private university hasstrong motivation in enterpreneurship. 2)From Chi Square, firstly, there is different motivation student depend on faculty selection. Secondly, there is different motivation depend on their parent’s work. Thirdly, there is no student motivation difference depend on ever or neverfollow enterpreneurship lecture.